2017
DOI: 10.1021/acs.analchem.7b01675
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurements of Mass and Collisional Cross-Section of Single Ions with Charge Detection Mass Spectrometry

Abstract: The masses and mobilities of single multiply charged ions of cytochrome c, ubiquitin, myoglobin, and bovine serum albumin formed by electrospray ionization are measured using charge detection mass spectrometry (CDMS). Single ions are trapped and repeatedly measured as they oscillate inside an electrostatic ion trap with cone electrodes for up to the maximum trapping time set at 500 ms. The histograms of the many single ion oscillation frequencies have resolved peaks that correspond to the different charge stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 54 publications
(102 reference statements)
1
73
0
Order By: Relevance
“…For these reasons, we devoted special attention to define K 0 and IM‐derived CCS values, and to clarify what influences these quantities. There are other methods than ion mobility spectrometry to determine experimental collision cross sections in a more direct way, for example, by monitoring the loss of ion signal due to collisions (Covey & Douglas, ; Chen, Collings, & Douglas, ; Anupriya, Jones, & Dearden, ; Anupriya et al, ; Dziekonski et al, ; Elliott et al, ; Sanders et al, ). These methods to determine collision cross sections are however not based on ion mobility measurements, and will not be covered here.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we devoted special attention to define K 0 and IM‐derived CCS values, and to clarify what influences these quantities. There are other methods than ion mobility spectrometry to determine experimental collision cross sections in a more direct way, for example, by monitoring the loss of ion signal due to collisions (Covey & Douglas, ; Chen, Collings, & Douglas, ; Anupriya, Jones, & Dearden, ; Anupriya et al, ; Dziekonski et al, ; Elliott et al, ; Sanders et al, ). These methods to determine collision cross sections are however not based on ion mobility measurements, and will not be covered here.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Williams and coworkers have shown that not only mass and charge but also cross-sectional information can be obtained by CDMS, which can be used to directly explore structures of heavy molecules. [84][85][86] Here, electrostatic mirrors at each side of the detection tube of the CDMS set-up have been implemented, and trapped ions collide with background gas, which leads to frequency shifts (see Figure 5). From the amount and the intervals of the frequency, the collisional cross section can be evaluated.…”
Section: The Added Value Of Charge Measurementsmentioning
confidence: 99%
“…For these reasons, we devoted special attention to define K 0 and IM-derived CCS values, and to clarify what influences these quantities. There are other methods than ion mobility spectrometry to determine experimental collision cross sections in a more direct way, for example, by monitoring the loss of ion signal due to collisions (Covey & Douglas, 1993;Chen, Collings, & Douglas, 1997;Anupriya, Jones, & Dearden, 2016;Anupriya et al, 2017;Dziekonski et al, 2017;Elliott et al, 2017;Sanders et al, 2018). These methods to determine collision cross sections are however not based on ion mobility measurements, and will not be covered here.…”
Section: Introductionmentioning
confidence: 99%